THE ISSUES OF FINANCIAL SUPPORT FOR LEGALLY WEDDED WIVES IN UNREGISTERED POLYGAMOUS MARRIAGES ACCORDING TO ISLAMIC FAMILY LAW PERSPECTIVE IN (NAGARI BATU BALANG, HARAU DISTRICT, LIMA PULUH KOTA REGENCY) - betni zahara; Yustiloviani Yustiloviani (UIN Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the problematic maintenance of legal wives who are polygamous according to the perspective of Islamic family law in Nagari Batu Balang, Kecamatan Harau, Kabupaten Lima Puluh Kota. This research was a field research with a qualitative descriptive approach method. Data collection techniques were conducted through interviews and documentation. The data sources used included primary data sources of 5 husbands who commit siri polygamy, 5 legitimate wives of siri polygamists, 3 siri wives of siri polygamists, and Ninik Mamak. Secondary data sources included books and journals related to the problematic maintenance of legitimate wives who were polygamous. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing and data verification. Data validity assurance techniques used source triangulation. The results showed that the problematic maintenance of legal wives who are polygamous in Nagari Batu Balang, Kecamatan Harau, Kabupaten Lima Puluh Kota, found that husbands prioritize maintenance to siri wives compared to legal wives, such as spending money that was not sufficient for daily needs and husbands were unfair in their turn to spend the night with their legal wives, focusing more on their siri wives. One of the factors that causes husbands to prioritize giving maintenance to siri wives is that husbands had daughters from their siri wives. Judging from the review of Islamic family law, the problematic maintenance of legal wives who were polygamous siri in Nagari Batu Balang was not in accordance with the rules of polygamy in Islam.